Encyclopedia of the alkaline earth compounds - Ropp, R. C. (Elsevier, 2013)
The book is a compilation describing the physical and chemical properties of all of the alkaline earth compounds that have been elucidated to date in the scientific literature (Nov. 2011). It will be valuable to students and researchers who wish to determine what is known about a specific compound. The concise descriptions presented of the chemical, physical and electrical properties of any given compound will serve as an introduction to the field to the non chemists. Such compounds are used in applications such as LEDs and the electronic devices like the current rash of wi-fi portable "telephones" (iPhones - actually small computers) and i-Pads. Structures and phase diagrams are presented where applicable. Additionally, preparation methods for each compound are presented to show which methods have been successful in creating the compound under discussion. This compendium is very valuable to students and scientific researchers in all fields of scientific endeavors, including those who are not chemists. Presents a systematic coverage of all known alkaline earth inorganic compounds and their propertiesProvides a clear consistent presentation based on groups and facilitates easy comparisons with each otherIncludes the structure of all the compounds in high quality full colour graphics Summarizes all currently known properties of the transition metals compounds Lists the uses and applications of these compounds in electronics, energy and catalysis.